Natural vacuum distillation for seawater desalination – A review. Issue 56 (1st December 2016) - Rashid, Ajaz; Ayhan, Teoman; Abbas, Abderrahim
Abstract: The availability of fresh drinking water is one of the biggest concerns today. It is a bigger challenge for arid and semi-arid areas. In these regions, desalination is heavily relied upon for meeting freshwater demands. Many processes for desalination have been introduced in an effort to minimize the use of non-renewable energy sources and cut down on pollution. The purpose of this study was to present a review on one such process, namely the natural vacuum distillation (NVD). NVD uses the barometric height of water column (approximately 10.3 m) to generate a "natural vacuum" in the headspace above the water column. This low-pressure environment makes it possible to carry out the desalination process at low temperatures, which can be easily attained from renewable energy sources or from waste heat sources. Another benefit of such a process is that mechanical pumping is required only for start-up, hence reducing power requirements. This paper presents a review of the work carried out on the NVD process so far, the different systems that have been designed using this principle and the major factors that affect the production of water using this technology. Additionally, it points out the areas that need to be investigated further and underscores the future prospects of the NVD process.